Identification of Sexsual Behavior and HIV Insidence on Public Transportation Driver in Sidoarjo - Fufa Nandasari; Lucia Y Hendrati (Universitas Airlangga, 2015)
Human Immunodeficiency Virus (HIV) is a virus that may degrade human immune system. This is resulting from interaction between agent, host, environment. Viewed from year to year, case of HIV-AIDS on all parts of world is keep increasing, therefore  this  disease  become  health  problem  feeling  concerned about  to  the  society,  because beside the vaccine and drug for the prevention of this not yet been found, this disease not generate symptom during its natural history. The objectives of this research were to analyze high risk sexual behavior causing HIV to the drivers of public transportation in Sub-Province Sidoarjo Those were sexual couple during last month, frequency of intercourse with another during last one mont, and usage of condom when doing intercourse with another. This was cross sectional study with the population were all drivers of public transportation who come to follow Voluntary Counseling and Testing (VCT) examination. There were 62 respondents who came to follow it. Data collection was conducted through interview, admission filling of questionnaire and observation. The results than studied by using existing theory. The result of this research showed that any 5% of drivers with positive result of HIV, with risk behavior 22,8% doing intercourse with wife and whore, 4,8% with whore only, 62,9% of them were not use condom while doing intercourse. to reduce risk exposed to HIV, it is recommended to increase their knowledge and give motivation about contagious risk of HIV. Keywords: Human Immunodeficiency Virus (HIV), the number of couple, sexual frequency, condom utilization, public transportation driver